Formalising the Informal through GST: Evidence from a Survey of MSMEs. Issue 2 (December 2022) - Ghosh, Sangeeta
In this study, the processes and channels through which an indirect tax reform has impacted micro, small and medium enterprises in India are identified using a field survey of small businesses. The Goods and Services Tax introduced in 2017 in India has been a significant departure from the past to impact businesses and business practices in a way that introduces formal practices into the everydayness of small businesses. This study shows that established informal mechanisms have been disturbed, which has led to coping mechanisms that have borne adverse outcomes for small businesses and workers involved in them. The benefits from such a move have been rather limited for small businesses. This study advocates that the quest to transition from an informal to a formal economy is one where many small steps must be first identified, and necessary handholding and training for the vulnerable units must be provided for inclusive development.